THE ROLE OF CONSUMER PRIVACY AND SECURITY ON BRAND LOYALTY - Drina Intyaswati (Jurnal InterAct, 2017)
Electronic commerce (e-commerce) touches almost all types of products and services. The increasing volume of online transactions online has raised consumer concerns about the data that has been given, what the company actually do with the information collected and eventually have access to it. Privacy issues have been identified as an important thing for consumers. The perception of online transaction security is also becoming a more important concern. Furthermore, we want to know how consumer security and privacy issues of consumers influence on brand loyalty, also be seen how the role of brand trust as a mediating relationship between consumer safety and brand loyalty, and relationships between consumer privacy and brand loyalty. This research is a quantitative survey method, in an effort to develop an empirical model to test the effect of consumer privacy and security consumers on brand loyalty. Samples used 100 peoples, drawn from the public to the age of 15-64 years (working age) in the region Sawangan - Depok. Analysis of data using regression analysis with SPSS program package. The results show that the consumer security and consumer privacy each affects brand loyalty, and there is a mediator in the influencing consumer privacy on brand loyalty, it means that the existence of brand trust will reduce the influence of consumer privacy on brand loyalty.